Indonesia's Public Wealth : A Balance Sheet Approach to Fiscal Policy Analysis - El Rayess, Majdeline; Halstead, Avril; Harris, Jason; Ralyea, John. (Washington, D.C. : International Monetary Fund, 2019)
Public sector balance sheets (PSBS) provide a framework for comprehensive and deep analysis of fiscal risks and policies. To illustrate these benefits, this paper shows how PSBS analysis can be applied to assess risks to Indonesia's public sector stemming from its public corporations. The paper also shows that the government's plans to finance a ramp-up in public investment with additional tax revenue increases both economic growth and public wealth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet